Environmental impact of mining and mineral processing management, monitoring, and auditing strategies - Jain, Ravi 1935- (Butterworth-Heinemann, 2016)
Environmental Impact of Mining and Mineral Processing: Management, Monitoring, and Auditing Strategies covers all the aspects related to mining and the environment, including environmental assessment at the early planning stages, environmental management during mine operation, and the identification of major impacts. Technologies for the treatment of mining, mineral processing, and metallurgical wastes are also covered, along with environmental management of mining wastes, including disposal options and the treatment of mining effluents. Presents a systematic approach for environmental assessment of mining and mineral processing projects. Provides expert advice for the implementation of environmental management systems that are unique to the mining industry. Effectively addresses a number of environmental challenges, including air quality, water quality, acid mine drainage, and land and economic impacts. Explains the latest in environmental monitoring and control systems to limit the environmental impact of mining and processing operations
Includes bibliographical references and index
Keywords: TECHNOLOGY & ENGINEERING / Mining; Green technology; Mineral industries / Environmental aspects; Mines and mineral resources / Environmental aspects; Umwelt; Mines and mineral resources -- Environmental aspects; Mineral industries -- Environmental aspects; Bergwerk; Mineralischer Rohstoff; Umweltbelastung